2005
DOI: 10.1089/cap.2005.15.628
|View full text |Cite
|
Sign up to set email alerts
|

Serum Zinc Correlates with Parent- and Teacher- Rated Inattention in Children with Attention-Deficit/Hyperactivity Disorder

Abstract: These findings add to accumulating evidence for a possible role of zinc in ADHD, even for middle-class Americans, and, for the first time, suggest a special relationship to inattentive symptoms. They do not establish either that zinc deficiency causes ADHD nor that ADHD should be treated with zinc. Hypothesis-testing clinical trials are needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
66
1
1

Year Published

2005
2005
2016
2016

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 110 publications
(70 citation statements)
references
References 17 publications
2
66
1
1
Order By: Relevance
“…Arnold et al (1990) reported that 18 children with Diagnostic and Statistical Manual of Mental Disorders, 3rd edition, revised (DSMIII-R) ADHD had 30% lower 24-hour urine zinc than 7 normal controls, suggesting either lower dietary intake or poorer absorption rather than zinc-wasting metabolism. In a companion paper (Arnold et al, 2005), we report on a negative correlation of serum zinc with parent-and teacher-rated inattentive symptoms (r = -45, p = 0.004). Bekaroglu et al (1996) concluded, " .…”
Section: Zinc In Adhdmentioning
confidence: 88%
See 1 more Smart Citation
“…Arnold et al (1990) reported that 18 children with Diagnostic and Statistical Manual of Mental Disorders, 3rd edition, revised (DSMIII-R) ADHD had 30% lower 24-hour urine zinc than 7 normal controls, suggesting either lower dietary intake or poorer absorption rather than zinc-wasting metabolism. In a companion paper (Arnold et al, 2005), we report on a negative correlation of serum zinc with parent-and teacher-rated inattentive symptoms (r = -45, p = 0.004). Bekaroglu et al (1996) concluded, " .…”
Section: Zinc In Adhdmentioning
confidence: 88%
“…Specifically, of nine published samples, two were Polish, two Turkish, one Iranian, one Israeli, two English, and only one American, with an additional American sample being published in a companion article (Arnold et al, 2005). This also raises questions about how similar the diagnostic procedures were to U.S. practice.…”
Section: Cautions and Limitationsmentioning
confidence: 99%
“…Most of these studies have focused on zinc and are consistent with the findings of our study. For example, a study by Arnold et al was conducted on 48 children and suggested that lower levels of zinc were associated with inattentiveness in children with ADHD (29). In another study in 2011, Arnold et al stated that taking zinc supplements alone would reduce ADHD symptoms in children (30).…”
Section: Discussionmentioning
confidence: 99%
“…Hence, zinc deficiency in the brain would be expected to lead to the build-up of amyloid-β, a key factor in the development of Alzheimer's disease. Zinc deficiency has also been implicated in autism [225] and ADHD [226,227]. Zinc is released into the synapse along with the neurotransmitter glutamate, and it is required for memory function and the maintenance of synaptic health as we age [228].…”
Section: A Role For Zinc Deficiencymentioning
confidence: 99%